2008
DOI: 10.1002/ps.1569
|View full text |Cite
|
Sign up to set email alerts
|

The drug transporter MgMfs1 can modulate sensitivity of field strains of the fungal wheat pathogen Mycosphaerella graminicola to the strobilurin fungicide trifloxystrobin

Abstract: It is concluded that the drug transporter MgMfs1 is a determinant of strobilurin sensitivity of field strains of M. graminicola.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 155 publications
(174 reference statements)
1
32
0
Order By: Relevance
“…In one of these populations, all strains had mutations in a zinc cluster transcription factor–encoding gene, mrr1 , causing overexpression of the ABC transporter AtrB (Kretschmer et al 2009). Resistance to sterol demethylation inhibitors and strobilurins in field isolates of Penicillium digitatum and Mycosphaerella graminicola , respectively, was also described (Nakaune et al 1998; Roohparvar et al 2008). Our work using a subtropical wild population of N. crassa (Ellison et al 2011; Palma-Guerrero et al 2013) further supports that natural variation to drug tolerance occurs and seems to be mediated by zinc cluster transcription factors.…”
Section: Discussionmentioning
confidence: 98%
“…In one of these populations, all strains had mutations in a zinc cluster transcription factor–encoding gene, mrr1 , causing overexpression of the ABC transporter AtrB (Kretschmer et al 2009). Resistance to sterol demethylation inhibitors and strobilurins in field isolates of Penicillium digitatum and Mycosphaerella graminicola , respectively, was also described (Nakaune et al 1998; Roohparvar et al 2008). Our work using a subtropical wild population of N. crassa (Ellison et al 2011; Palma-Guerrero et al 2013) further supports that natural variation to drug tolerance occurs and seems to be mediated by zinc cluster transcription factors.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, C. glabrata homologs of DHA1 Qdr2 (Costa et al, 2013a), Aqr1 (Costa et al, 2013b), and Tpo3 (Costa et al, 2014) have been implicated in antifungal drug resistance, while the homolog of Aqr1 and Tpo3 were further shown to have a role in acetic acid resistance and polyamine homeostasis, respectively (Costa et al, 2013b, 2014). In phytopathogenic fungi, which constitute an important problem in crop protection, MDR/MXR-MFS transporters such as BcMfs1 from Botrytis cinerea (Hayashi et al, 2002) and MgMfs1 from Mycosphaerella graminicola (Roohparvar et al, 2007, 2008) have also been shown to be involved in resistance to natural plant toxins and fungicides. Altogether, the role of many DHA transporters from fungal species was found to, at least partially, mirror their S. cerevisiae homologs, highlighting the relevance of studies in the model yeast to elucidate the regulation and functional role of these transporters in other species.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…In the budding yeast, MFS transporters containing either a 12- or 14-transmembrane domain have been demonstrated to confer resistance to a wide array of chemicals and drugs [3] and their regulation has been found to be controlled by several stress related transcription factors including Yap1, Msn2, Msn4, and Sfp1 [2]. In phytopathogenic fungi, MFS transporters have been shown to be involved in resistance to toxins and fungicides [48]. …”
Section: Introductionmentioning
confidence: 99%